The effect of ground motion vertical component on the seismic response of historical masonry buildings: The case study of the Banloc Castle in Romania. (15th December 2021) - Chieffo, Nicola; Mosoarca, Marius; Formisano, Antonio; Lourenço, Paulo B.; Milani, Gabriele
Highlights: The effect of VGM on the Romanian historical masonry building is analysed. The ground motion vertical component has a high-frequency content in the time domain. Spectral V/H PGA ratios are period-dependent for short vibration periods. The decompressive seismic action reduces the capacity of masonry structural elements. The VGM increases the global vulnerability by the activation of failure mechanisms. Abstract: The current paper aims at analysing the effect of ground motion vertical component in the case of near-field excitations on the structural response of historical masonry buildings. In this perspective, the Banloc Castle in Romania has been considered as a reference case study. This historical masonry structure was damaged by the Banat-Voiteg earthquake that occurred in December 1991 in the homonymous city. To this purpose, a FEM model of the building, set up using the DIANA FEA analysis software, has been studied in the non-linear dynamic field considering a real ground motion record based on specific source-to-site distance, moment magnitude and focal depth. The effects of the impulsive earthquake have been evaluated considering the main engineering demand parameters, such as displacements and forces, focusing on two different scenarios, namely horizontal and horizontal + vertical ground motions. The obtained results have shown that the vertical ground motion sensibly modifies the structural capacity of the building since it produces a relevant modification of the in-plane walls behaviour and the stress conditions. Important considerations about the behaviour (or seismic response modification) factor, ductility and stress in terms of axial and shear forces have been provided. Moreover, numerical damage patterns have been compared to the real cracks detected. Finally, a set of fragility curves has been derived taking into consideration the near-field effects.